Synthesis and evaluation of 1, 4–naphthoquinone ether derivatives as SmTGR inhibitors and new anti‐schistosomal drugs. (3rd August 2015) - Johann, Laure; Belorgey, Didier; Huang, Hsin‐Hung; Day, Latasha; Chessé, Matthieu; Becker, Katja; Williams, David L.; Davioud‐Charvet, Elisabeth
<x xml:space="preserve">Abstract</x> Investigations regarding the chemistry and mechanism of action of 2‐methyl‐1, 4‐naphthoquinone (or menadione) derivatives revealed 3‐phenoxymethyl menadiones as a novel anti‐schistosomal chemical series. These newly synthesized compounds (1–7) and their difluoromethylmenadione counterparts (8, 9) were found to be potent and specific inhibitors of Schistosoma mansoni thioredoxin‐glutathione reductase (SmTGR), which has been identified as a potential target for anti‐schistosomal drugs. The compounds were also tested in enzymic assays using both human flavoenzymes, i.e. glutathione reductase (hGR) and selenium‐dependent human thioredoxin reductase (hTrxR), to evaluate the specificity of the inhibition. Structure–activity relationships as well as physico‐ and electro‐chemical studies showed a high potential for the 3‐phenoxymethyl menadiones to inhibit SmTGR selectively compared to hGR and hTrxR enzymes, in particular those bearing an α‐fluorophenol methyl ether moiety, which improves anti‐schistosomal action. Furthermore, the (substituted phenoxy)methyl menadione derivative (7) displayed time‐dependent SmTGR inactivation, correlating with unproductive NADPH‐dependent redox cycling of SmTGR, and potent anti‐schistosomal action in worms cultured ex vivo. In contrast, the difluoromethylmenadione analog 9, which inactivates SmTGR through an irreversible non‐consuming NADPH‐dependent process, has little killing effect in worms cultured ex vivo. Despite ex vivo activity, none of the compounds tested was active in vivo, suggesting that the limited bioavailability may compromise compound activity. Therefore, future studies will be directed toward improving pharmacokinetic properties and bioavailability.